CRYPTOCURRENCY FROM SHARIA PERSPECTIVE - Octaviana, Fitri Anni; Nurhisam, Luqman (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2026)
Cryptocurrency has become a significant innovation in the digital financial system, sparking various perspectives on its compatibility with sharia. This study aims to analyze the legality of cryptocurrency from a sharia perspective, including its transaction mechanisms and investment implications. The primary focus is on examining the elements of gharar (uncertainty) and maysir (gambling), which could potentially render it impermissible under sharia. The research employs a normative analysis approach to explore contemporary scholars' views and their relevance to maqasid sharia, which emphasize the protection of wealth and societal welfare. The findings indicate that, despite cryptocurrency's benefits, such as transaction efficiency and accessibility, its high speculative risks and value uncertainty pose major obstacles to its acceptance under sharia. Therefore, clear and comprehensive regulations are needed to accommodate cryptocurrency use in sharia-compliant financial institutions without violating Islamic principles. This study provides a significant contribution to clarifying the position of cryptocurrency within the Islamic financial system and encourages the development of sharia-based regulations for digital transactions.